Sex and Geographic Differences in the Prevalence of Reported Childhood Motor Disability and Their Trends in Taiwan. (5th April 2018) - Tsai, Cheng-Fang; Guo, How-Ran; Tseng, Yen-Cheng; Lai, Der-Chung
Abstract : Motor disability (MD) is not uncommon in children, but data at the national level are scarce. As the Taiwan government certifies and registers disabled residents for providing services on a routine basis, the registry provides a unique opportunity for studying MD. Using data from the registry, we calculated the prevalence of MD by age, sex, and geographic area and assessed the changes from 2004 to 2010. We excluded cases under 3 years old because the government discourages the certification at this age. We found that cases between 3 and 17 years old decreased from 8187 to 6022 per year from 2004 to 2010 and the prevalence generally decreased every year in all age groups. There were more boy cases than girl cases every year, and the prevalence rate ratios ranged from 1.26 to 1.39 (p < 0.05 in all years), with a decreasing trend over time (p < 0.01 ). Rural areas had higher prevalence in all the years, and the prevalence rate ratio decreased from 1.31 to 1.23 (p < 0.05 in all years), with a decreasing trend over time (p < 0.05 ). Further studies identifying the risk factors contributing to the decreases might help in the prevention of MD in the future.